Tiny Encryption Algorithm on Discrete Cosine Transform Watermarking - Diaztary, Windy; Atmajaya, Dedy; Umar, Fitriyani; Purnawansyah; Harlinda; Abdullah, Syahrul Mubarak (2021 3rd East Indonesia Conference on Computer and Information Technology (EIConCIT), 2021)
Watermarking is a method embeds a secret imformation into a host such that can not be detected by the human senses. Hiding the secret information such as legal ownership is a part of information security. In this research, Tiny Encryption Algorithm (TEA) is implemented on watermarking using Discrete Cosine Transform (DCT) to add strenghten information security. We analyze the security of TEA using Avalanche Effect and the effect when implemented on DCT watermarking in terms of imperceptibility. Secret text is encrypted then embedded into image using the DCT. The results of the embedding are then extracted to obtain the hidden text, then proves the image belongs to the copyright holder by decrypting the extracted results. Testing results using Avalanche effect obtained value of 49.25% which is strong and good for encryption. The effect of TEA on DCT watermarking shows that the encryption does not destroy the host image.